2021
DOI: 10.1007/s00268-021-06315-w
|View full text |Cite
|
Sign up to set email alerts
|

National Trends and Perioperative Outcomes of Robotic‐assisted Hepatectomy in the USA: A Propensity‐score Matched Analysis from the National Cancer Database

Abstract: Background A paucity of data exists on the national use of robotic hepatectomy. We assessed national trends and perioperative outcomes of robotic hepatectomy in the USA. In addition, factors associated with use of the robotic approach were analyzed. Methods The National Cancer Database (NCDB) was queried for patients undergoing hepatectomy from 2010 to 2016. Patients undergoing total hepatectomy for transplant were excluded. Factors associated with the use of the robotic approach were assessed using logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The superior short-term outcomes observed in this study, such as less blood loss, less postoperative complications, and shorter length of stay, are in line with randomised controlled trials such as the OSLO-COMET[ 26 ] and the LapOpHuva [ 27 ] and with several observational studies [ 28 32 ] and a recent meta-analysis [ 33 ]. This study confirmed that the two techniques showed comparable R0 resections and comparable overall survival in the matched cohorts.…”
Section: Discussionsupporting
confidence: 85%
“…The superior short-term outcomes observed in this study, such as less blood loss, less postoperative complications, and shorter length of stay, are in line with randomised controlled trials such as the OSLO-COMET[ 26 ] and the LapOpHuva [ 27 ] and with several observational studies [ 28 32 ] and a recent meta-analysis [ 33 ]. This study confirmed that the two techniques showed comparable R0 resections and comparable overall survival in the matched cohorts.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, the higher rate of achievement of TO may represent the ability to accomplish better patient care and long‐term outcomes 39 . Previous studies have noted that increasing adoption of MIS to treat HPB cancers over the last decade, leading to an increased rate of achieving TO 20,40 . Collectively, to achieve the best possible outcomes for all patients, it is imperative to implement additional measures that promote equitable access to MIS, particularly for individuals who have been disproportionately affected by long‐standing poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Still, only 2.5% of all hepatectomies, major or minor, were performed robotically. 118 While early results look promising for the future of RH, there are several limitations to the current literature. First, as previously mentioned, no RCTs for primary liver cancer have been published to date.…”
Section: Penetrance Of Robotic Hepatectomymentioning
confidence: 99%
“…From 2010 to 2016, Kamel et al found a significant increase in utilization of RH, from 0.8% to 4.1% ( p < 0.001). Still, only 2.5% of all hepatectomies, major or minor, were performed robotically 118 …”
Section: Hepato‐pancreato‐biliary Surgerymentioning
confidence: 99%